Las competencias pedagógicas de los docentes para la instrucción de estudiantes con capacidades diferentes en la unidad educativa técnico Arenillas del cantón Arenillas provincia de El Oro periodo 2014 - 2015. - Guillén Granda, Jairo Eduardo (2015)
Inclusive education has an approach that takes its emphasis on assessment of educational diversity as one of the main enriching parts of the teaching-learning process and based on this human development is favored. It is accepted that we are all different and that differences are essential for humans. Given this, the school must raise new teaching strategies that take into account and respond to the different characteristics presented by students.